7. Training of Artistic Skills of the Music Teacher - Tetelea Margarita (Sciendo, 2020)
In this article, concepts such as "creativity" and "artistic creativity", based on the ideas of a number of famous scholars, are dealt with. The concept of "creativity" is defined according to the aspiration of an artistic person to self-expression. Speaking about the structure and the components of the creative process, we have identified the factors that enhance the development of the creative abilities of the students from the pedagogic-artistic specialties in the process of designing the didactic-artistic approach. It is also reflected in the diversity of these factors: psychological, pedagogical, didactic, artistic. In conclusion, the emphasis is on the fact that self-expression in artistic creativity is the individual's need, and need is classified as aesthetic.